Optimizing Maximal Fat Oxidation Assessment by a Treadmill-Based Graded Exercise Protocol: When Should the Test End? - Amaro-Gahete, Francisco J.; Sanchez-Delgado, Guillermo; Helge, Jørn W.; Ruiz, Jonatan R. (Frontiers in Physiology, 2019)
Maximal fat oxidation during exercise (MFO) and the exercise intensity eliciting MFO (Fatmax) are considered important factors related to metabolic health and performance. Numerous MFO and Fatmax data collection and analysis approaches have been applied, which may have influenced their estimation during an incremental graded exercise protocol. Despite the heterogeneity of protocols used, all studies consistently stopped the MFO and Fatmax test when the respiratory exchange ratio (RER) was 1.0. It remains unknown however whether reaching a RER of 1.0 is required to have an accurate, reliable and valid measure of MFO and Fatmax. We aimed to investigate the RER at which MFO and Fatmax occurred in sedentary and trained healthy adults. A total of 177 sedentary aged between 18-65 years participated in the study. MFO and Fatmax were calculated by an incremental graded exercise protocol before and after 2 exercise-based intervention. Our findings suggest that a graded exercise protocol aiming to determine MFO and Fatmax could end when a RER=0.93 is reached in sedentary healthy adults, and when a RER=0.90 is reached in trained adults independently of sex, age, body weight status, or the Fatmax data analysis approach. In conclusion, we suggest reducing the RER from 1.0 to 0.95 to be sure that MFO is reached in outliers individuals. This methodological consideration has important clinical implications, since it would allow to apply smaller workload increments and/or to extend the stage duration to attain the steady-state, without increasing the test duration.